Family ownership and corporate environmental responsibility: The contingent effect of venture capital and institutional environment - Zhu Zhu; Feifei Lu (Journal of Risk and Financial Management, 2020)
As scholars and policy makers pay more attention to the environmental impact of economic activities, more focus has been placed on the corporate environmental responsibility (CER) of family firms, which accounts for the majority of businesses in both developed and developing countries. Using a sample of 4714 private enterprises across 23 provinces in China, the current study examines the effect of family ownership on CER investment, as well as the moderating effects of venture capital investment and local institutional development. Results show that concentrated family ownership leads to lower CER spending, however, when venture capital investment comes from developed markets, the negative relationship is reversed. In addition, the marketization level of the province in which a family firm is headquartered mitigates the negative relationship between family ownership and CER investment.
Keywords: 330; corporate environmental responsibility; venture capital; institutional development; family ownership; emerging market